8.5k views
1 vote
Sec (90 -A) sinA = cot (90-A). tan( 90- A)​

User Jan Molak
by
4.9k points

2 Answers

4 votes

L.H.S=sec(90-A)·sinA

=cosecA·sinA ;[sec(90-A)= cosecA]

=1/sinA·sinA ;[cosecA=1/sinA]

=1

R.H.S=cot(90-A)·tan(90-A)

=tanA·cotA ;[cot(90-A)=tanA, tan(90-A)=cotA]

=tanA·1/tanA ;[cotA=1/tanA]

=1

thus, L.H.S=R.H.S

[Proved]

User Omair Nabiel
by
4.8k points
6 votes

Explanation:

sec(90-A) . Sin A = cot (90-A) . tan(90-A)

cosec X sinA = tanA X cotA

1/sinA X sinA = tanA X 1/tanA

1=1

Hence proved

User Jigneshsinh Rathod
by
5.5k points